Features of the ontological approach to art in philosophy - Boranbayev, A.A.; Nurmanbetova, J.N.; Bolyssova, K.M. (Karagandy University of the name of acad. E.A. Buketov, 2025)
This article examines art from an ontological perspective. Classical and contemporary philosophical concepts that explain the essence of art, its significance, and its role in human life were considered. The author explored art not merely as an aesthetic phenomenon but as a fundamental manifestation of human existence. The interrelation between art and reality, the existential and metaphysical dimensions of artistic creativity, as well as the epistemological, axiological, and communicative aspects of art, were analyzed. The article discussed the ideas of thinkers such as Plato, Aristotle, Heidegger, and Gadamer regarding the ontological foundations of art and offers new perspectives on its existential significance. At the present stage, the reconsideration of the ontological meaning of art has become an urgent issue. Is art merely a reflection of reality, or does it shape reality itself? What is its relation to being? These questions occupy an essential place in philosophical discourse. Particularly in the postmodern era, the relationship between art and reality has become even more complex. This article conducts an ontological analysis of art, examining its relation to being and truth. Additionally, the ontological foundations of art are explored within the context of Kazakhstani philosophy and culture.
Keywords: metaphysics; postmodernism; existentialism; aesthetics; reality; being; ontology; art